2014
DOI: 10.1097/iae.0000000000000008
|View full text |Cite
|
Sign up to set email alerts
|

Endophthalmitis Associated With Intravitreal Injections

Abstract: The rate of clinically suspected endophthalmitis after IVIs is low whether the procedure is performed in the office or operating room setting. The findings have implications in terms of the patient convenience, efficiency, and cost of administrating these treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…This has also been confirmed by a literature review summarizing data of 445,503 IVI, which did not show a significant difference between OR [71, 72, 78, 79] and office-based IVI [67-70]. …”
Section: Peri- /Injection Management In Intravitreal Pharmacotherapymentioning
confidence: 54%
See 1 more Smart Citation
“…This has also been confirmed by a literature review summarizing data of 445,503 IVI, which did not show a significant difference between OR [71, 72, 78, 79] and office-based IVI [67-70]. …”
Section: Peri- /Injection Management In Intravitreal Pharmacotherapymentioning
confidence: 54%
“…A consecutive case series including a total of 11,710 IVI and comparing office-based (8,647) and OR (3,063) settings reported no significant difference in EO rates (0.035 and 0.065%, respectively) [78]. This has also been confirmed by a literature review summarizing data of 445,503 IVI, which did not show a significant difference between OR [71, 72, 78, 79] and office-based IVI [67-70].…”
Section: Peri- /Injection Management In Intravitreal Pharmacotherapymentioning
confidence: 99%
“…The difference in endophthalmitis rates may be a reflection of socioeconomic or other factors [39]. Tabendeh et al [30] reported an endophthalmitis rate of 3/8,210 (0.037%) anti-VEGF injections in the office compared with 2/3,047 in the operating room (0.066%), in another non-randomised study that was not powered to be able to detect a difference. Compared with office-based injections, there was no apparent benefit to an OR environment in this small study.…”
Section: Reviewmentioning
confidence: 99%
“…Delayed-onset bleb-related endophthalmitis is also associated with a disproportionately higher rate of Streptococcal infection. This may be the result of alterations in the resident flora or structural changes in the eye wall, and such changes may also occur in some eyes after multiple intravitreal injections [30, 84–86]. …”
Section: Reviewmentioning
confidence: 99%
“…Elevation of IOP that is recalcitrant to maximal medical therapy can be successfully managed by vitrectomy to remove the steroid from the eye [77]. Endophthalmitis after intravitreal injection of IVTA is reported to occur at a similar rate as after other intravitreal injections with no difference in the rate in the office versus operating room settings and an overall rate of endophthalmitis after intravitreal injection of 0.043 % [78]. No benefit is found with topical antibiotics before or after intravitreal injections and there is a trend toward an increase in the rate of endophthalmitis with the use of topical antibiotics [79,80].…”
Section: Triamcinolone Acetonidementioning
confidence: 99%